2023
DOI: 10.1177/00208523231164587
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the perception of digital government and artificial intelligence in the public sector in Jalisco, Mexico

Abstract: The advancement and continuous development of information and communication technologies highlights the importance of analysing and monitoring the development and capabilities of governments to use and exploit the potential of new technologies. Digital government and artificial intelligence in the public sector are two trends associated with technological development. This research conducts an analysis of these elements from the perspective of public officials by conducting a factor analysis. The study is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study aligns with the reasoning and argumentation found in the existing literature (e.g. Bharadwaj, 2000; Mikalef et al , 2023; Ruvalcaba-Gomez and Cifuentes-Faura, 2023), which posits that the RBT can offer advantages to the IS field. Specifically, the RBT serves as a basis for specifying resources at the organizational level, enables differentiation between cross-functional, technical and nontechnical resources and facilitates systematic examination of the relationship between aggregated resources and capabilities, ultimately impacting key performance outcomes in domains such as the 4IR, blockchain technology, sustainability and the circular economy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study aligns with the reasoning and argumentation found in the existing literature (e.g. Bharadwaj, 2000; Mikalef et al , 2023; Ruvalcaba-Gomez and Cifuentes-Faura, 2023), which posits that the RBT can offer advantages to the IS field. Specifically, the RBT serves as a basis for specifying resources at the organizational level, enables differentiation between cross-functional, technical and nontechnical resources and facilitates systematic examination of the relationship between aggregated resources and capabilities, ultimately impacting key performance outcomes in domains such as the 4IR, blockchain technology, sustainability and the circular economy.…”
Section: Discussionsupporting
confidence: 89%
“…Scholars contend that the integration of AI within the government sector offers novel avenues for enhancing OC. They propose that to gain a deeper comprehension of the development of innovative tools for OP, it is imperative to tackle the challenges associated with the AI productivity paradox (Akter et al , 2023; Ruvalcaba-Gomez and Cifuentes-Faura, 2023). To acquire value, AIC must generate a collection of organizational and AI resources (Pan and Nishant, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, researchers have focused on analyzing the governance of the so-called “Fourth Industrial Revolution,” as there is an urgent need to understand the norms, policies, and institutions that will attempt to generate artificial intelligence (AI)-based welfare and social progress (Ruvalcaba-Gomez and Cifuentes-Faura, 2023). Notwithstanding the potential benefits of AI, there is some interest in knowing the pernicious effects, unexpected outcomes, and unintended consequences of AI (McEvoy, 2019; Sun and Medaglia, 2019).…”
Section: Introductionmentioning
confidence: 99%